Microarray analysis of long‐noncoding RNAs and mRNA expression profiles in human steroid‐induced avascular necrosis of the femoral head. Issue 9 (12th May 2019) - Luo, Hongbin; Lan, Weibin; Li, Yongfeng; Lian, Xiaolan; Zhang, Nanwen; Lin, Xinhua; Chen, Peng
Abstract: This study performed the first microarray analysis of long‐noncoding RNA (lncRNA) and mRNA expression profiles in human steroid‐induced avascular necrosis of the femoral head (SAVNFH). Expression levels of lncRNAs and mRNAs in three human SAVNFH samples and three human femoral head fracture samples (controls) were detected using third‐generation lncRNA microarrays (KangChen Biotech, Shanghai, China). The fold change, false discovery rate, and P value were utilized to filter genes with significant differential expression in the SAVNFH samples compared with the control samples. In total, there were 1179 upregulated and 3214 downregulated lncRNAs (P2. zerofold, P  < 0.05). Meanwhile, 1092 upregulated and 565 downregulated mRNAs were found in the SAVNFH samples compared with the control samples. Then, quantitative real‐time polymerase chain reaction was used to confirm the previous microarray results using 8 and 20 selected dysregulated lncRNAs and mRNAs, respectively, and the results generally confirmed the microarray findings. Finally, we used Gene Ontology (GO) and pathway analysis to investigate the functions of the altered mRNAs and their associated GO terms and biological pathways. The Immune system process term (GO:0002376) was the most significantly upregulated GO term, and the Regulation of blood coagulation term (GO:0030193) was the most significantly downregulated GO term in the biological process category for the SAVNFH samples. "Hematopoietic cell lineage ‐ Homo sapiens (human) (Pathway ID: hsa04640)" and "Complement and coagulation cascades ‐ Homo sapiens (human) (Pathway ID: hsa04610)" were the most significantly up‐ and downregulated pathways in the SAVNFH samples compared with the controls. In conclusion, the differential expression of lncRNAs and mRNAs may be correlated with the pathogenesis of SAVNFH, and these significantly dysregulated lncRNAs and mRNAs may function through networks or participate in several specific biological processes. Further research is needed to understand their exact functions and mechanisms in SAVNFH. Abstract : This is the first study to profile the expression of lncRNAs and mRNAs in human steroid‐induced avascular necrosis of the femoral head (SAVNFH) samples using microarray analysis, with the aim of detecting the correlation between SAVNFH and the expression levels of lncRNAs and mRNAs.